Increasing Marketing Effectiveness Through Appropriate Positioning Strategies In The Company PT. Waysata Indonesia Bahagia - Rais Aryadi Nurcahyo; Dr. Albari, M.Si (Cita konsultindo, 2024)
This research examines the process of implementing the positioning strategy carried out by PT Waysata Indonesia Bahagia. This research examines the STP (Segmenting, Targeting and Positioning) marketing strategy which is carried out with a focus on increasing the effectiveness of the positioning process and product positioning strategy implemented by PT Waysata Indonesia Bahagia. This research uses a qualitative method or approach with data collection tools using questionnaires and direct observation carried out by the author through internship activities carried out at the company involving three analysis units as sources for collecting data and information that is useful for research. The findings of this research are that the effectiveness of a positioning strategy can be achieved by a company starting from the right market segmentation process, clear positioning communication, active digital marketing, good partnership management, and the company's ability to adapt the strategy. Even though Instagram sales and visitor data show fluctuations, the company recognizes the importance of evaluating and adjusting its strategy periodically.